Tribute to Stafford Beer - Espejo, Raul (Kybernetes, 2004)
This paper explores the history of Stafford Beer's work in management cybernetics, from his early conception and simulation of an adaptive automatic factory and associated experimentation in biological computing, through the development of the Viable System Model and the Team Syntegrity technique for discussion and planning. It also pursues Beer into the fields of micro- and macropolitics and spirituality. The aim is to show that all of Beer's projects can be understood as specific instantiations and workings out of a cybernetic ontology of unknowability and becoming: a stance that recognises.